Meninges-derived cues control axon guidance - Suter, Tracey A.C.S. (Dev Biol, 2017)
The axons of developing neurons travel long distances along stereotyped pathways under the direction of extracellular cues sensed by the axonal growth cone. Guidance cues are either secreted proteins that diffuse freely or bind the extracellular matrix, or membrane-anchored proteins. Different populations of axons express distinct sets of receptors for guidance cues, which results in differential responses to specific ligands. The full repertoire of axon guidance cues and receptors and the identity of the tissues producing these cues remain to be elucidated. The meninges are connective tissue layers enveloping the vertebrate brain and spinal cord that serve to protect the central nervous system (CNS). The meninges also instruct nervous system development by regulating the generation and migration of neural progenitors, but it has not been determined whether they help guide axons to their targets. Here, we investigate a possible role for the meninges in neuronal wiring. Using mouse neural tissue explants, we show that developing spinal cord meninges produce secreted attractive and repulsive cues that can guide multiple types of axons in vitro. We find that motor and sensory neurons, which project axons across the CNS-peripheral nervous system (PNS) boundary, are attracted by meninges. Conversely, axons of both ipsi- and contralaterally projecting dorsal spinal cord interneurons are repelled by meninges. The responses of these axonal populations to the meninges are consistent with their trajectories relative to meninges in vivo, suggesting that meningeal guidance factors contribute to nervous system wiring and control which axons are able to traverse the CNS-PNS boundary.